2014
DOI: 10.1016/j.schres.2014.08.021
|View full text |Cite
|
Sign up to set email alerts
|

A randomized placebo-controlled pilot study of pravastatin as an adjunctive therapy in schizophrenia patients: Effect on inflammation, psychopathology, cognition and lipid metabolism

Abstract: Objective The aim of this study was to investigate the role of pravastatin, as an adjunctive therapy, on inflammatory markers, lipid and glucose metabolism, psychopathology, and cognition in subjects with schizophrenia and schizoaffective disorder. Methods Schizophrenia or schizoaffective subjects (N=60) were randomized to receive either a 12-week supply of pravastatin 40 mg/day or placebo treatment. Anthropometric measures, lipids and glucose metabolism, inflammatory markers, psychopathology and cognitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 43 publications
0
51
1
2
Order By: Relevance
“…Statin has been proposed as a novel treatment for the disorder, presumably based on its potential to ameliorate neuroinflammation 54 , and was tested in a small number of clinical trials. For instance, Vincenzi et al reported improvement in the Positive and Negative Syndrome Scale (PANSS) from baseline to 6 weeks with pravastatin although the effect failed to maintain at 12 weeks 55 . In another study, there was preliminary evidence that simvastatin improved PANSS scores, although the results were not statistically significant 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Statin has been proposed as a novel treatment for the disorder, presumably based on its potential to ameliorate neuroinflammation 54 , and was tested in a small number of clinical trials. For instance, Vincenzi et al reported improvement in the Positive and Negative Syndrome Scale (PANSS) from baseline to 6 weeks with pravastatin although the effect failed to maintain at 12 weeks 55 . In another study, there was preliminary evidence that simvastatin improved PANSS scores, although the results were not statistically significant 56 .…”
Section: Discussionmentioning
confidence: 99%
“…11 This observation is partially supported by clinical studies. For example statins have been shown to ameliorate SCZ symptoms in two small-scale clinical trials 62,63 . In one study simvastatin as adjunctive treatment was tested and there was preliminary evidence for improving total symptoms scores, but the result was not statistically significant 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Pilot studies of pravastatin and simvastatin, lipid lowering medications, have been conducted in schizophrenia patients. The preliminary findings from these trials also indicate these medications also provide a temporary reduction in inflammation, positive, and negative symptoms (Chaudhry et al, 2014; Vincenzi et al, 2014). However, larger scale clinical trials that consider their long-term effects are necessary to replicate and confirm long-term beneficial outcomes.…”
Section: Schizophrenia and Cardiovascular Diseasementioning
confidence: 96%